(Re)Producing Peruvian Professionals: State Welfare and Poor Quechua Mother’s Maternal Citizenship - Irons, Rebecca (2019)
Through the discourses of financial-independence and «professionalisation» of offspring promoted by state-provided healthcare and welfare (Juntos), Quechua women living in poverty find that upon entering motherhood their full citizenship becomes conditional on successful behaviours and stewardship of children to a more «desirable» livelihood than their own. This suggests that mothering- while-poor places a moral value on women that the state uses to justify monitoring and governing them.   This paper is based on one-year’s ethnographic-fieldwork in rural communities and health centres or posts in Vilcashuaman province, Ayacucho department, Peru. 100 interviews were conducted with women, men and health-workers, in addition to substantial participant-observation.   Whilst the pervasive discourses overburden women’s freedoms, there are alternatives to «professionalization» of indigenous youth that do not require the financial literacy currently imposed on mothers. This paper suggests that moral values placed on poor-maternities are sometimes used unfairly as a justification for reproductive-intervention and revocation of full-citizenship for poor, indigenous women.